MITIGATING CARGO DAMAGE IN CONTAINERISED SHIPPING: A HYBRID ASSESSMENT OF RISK FACTORS AND STRATEGIC INTERVENTIONS - ABU TALIB, NURUL AISYAH; OTHMAN, MOHAMMAD KHAIRUDDIN; MOHD ZAIDEEN, IZYAN MUNIRAH; MD HANAFIAH, RUDIAH; TARUDIN, NUR FARIZAN (Journal of Maritime Logistics, 2025)
The introduction of containerisation has profoundly transformed global trade by significantly improving efficiency of cargo handling and transportation processes. Nevertheless, cargo damage during transit continues to pose a considerable challenge, resulting in financial losses and deteriorating customer confidence. This study aims to identify and analyse the principal causes of cargo damage namely, machinery and equipment failure, human-related factors, marine incidents, environmental conditions, and theft as well as to evaluate strategies for mitigating these risks. Employing a structured methodology that integrates the spider web analytical technique with the average rating value method, the study prioritises these risk factors based on their relative impact. The findings indicate that proper maintenance of equipment and continuous personnel training are the most effective strategies for reducing cargo damage. The study offers practical recommendations for shipping companies seeking to improve operational safety, reliability, and overall efficiency in containerised freight transport.